Distinct Functions of Specialized Dendritic Cell Subsets in Atherosclerosis and the Road Ahead - Alma Zernecke (Scientifica)
Atherosclerotic vascular disease is modulated by immune mechanisms. Dendritic cells (DCs) and T cells are present within atherosclerotic lesions and function as central players in the initiation and modulation of adaptive immune responses. In previous years, we have studied the functional contribution of distinct DC subsets in disease development, namely, that of CCL17-expressing DCs as well as that of plasmacytoid DCs that play specialized roles in disease development. This review focuses on important findings gathered in these studies and dissects the multifaceted contribution of CCL17-expressing DCs and pDCs to the pathogenesis of atherosclerosis. Furthermore, an outlook on future challenges faced when studying DCs in this detrimental disease are provided, and hurdles that will need to be overcome in order to enable a better understanding of the contribution of DCs to atherogenesis are discussed, a prerequisite for their therapeutic targeting in atherosclerosis.